LRRK1 regulation of actin assembly in osteoclasts involves serine 5 phosphorylation of L‐plastin. Issue 12 (22nd August 2018) - Si, Mingjue; Goodluck, Helen; Zeng, Canjun; Pan, Songqin; Todd, Elizabeth M.; Morley, Sharon Celeste; Qin, Xuezhong; Mohan, Subburaman; Xing, Weirong
Abstract: Mice with disruption of Lrrk1 and patients with nonfunctional mutant Lrrk1 exhibit severe osteopetrosis phenotypes because of osteoclast cytoskeletal dysfunction. To understand how Lrrk1 regulates osteoclast function by modulating cytoskeleton rearrangement, we examined the proteins that are differentially phosphorylated in wild‐type mice and Lrrk1 ‐deficient osteoclasts by metal affinity purification coupled liquid chromatography/mass spectrometry (LC/MS) analyses. One of the candidates that we identified by LC/MS is L‐plastin, an actin bundling protein. We found that phosphorylation of L‐plastin at serine (Ser) residues 5 was present in wild‐type osteoclasts but not in Lrrk1 ‐deficient cells. Western blot analyses with antibodies specific for Ser5 phosphorylated L‐plastin confirmed the reduced L‐plastin Ser5 phosphorylation in Lrrk1 knockout (KO) osteoclasts. micro computed tomography (Micro‐CT) analyses revealed that the trabecular bone volume of the distal femur was increased by 27% in the 16 to 21‐week‐old L‐plastin KO females as compared with the wild‐type control mice. The ratio of bone volume to tissue volume and connectivity density were increased by 44% and 47% (both P < 0.05), respectively, in L‐plastin KO mice. Our data suggest that targeted disruption of L‐plastin increases trabecular bone volume, and phosphorylation of Ser5 in L‐plastin in the Lrrk1 signaling pathway may in part contribute to actin assembly in mature osteoclasts. Abstract : Lrrk1 regulates phosphorylation of L‐plastin knockout of L‐plastin causes osteopetrosis L‐plastin regulates osteoclast function